Clinical and electrophysiological characteristics of extra-pulmonary vein triggers in patients who underwent catheter ablation for atrial fibrillation. (24th May 2021) - Hwang, T; Yoon, M; Kim, M; Kim, I; Yu, H; Kim, T; Uhm, J; Kim, J; Joung, B; Lee, M; Pak, H
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Extra-pulmonary vein (PV) triggers play significant roles in atrial fibrillation (AF) recurrence after AF catheter ablation (AFCA). Purpose: We explore the clinical and electrophysiological characteristics of extra-PV triggers in de novo and repeat-AFCA procedure. Methods: We included 2, 151 patients who had de novo AFCA and 319 repeat AFCA (female 28.0%, 59.1 ± 10.8 years old, paroxysmal AF 65.1%) those underwent post-procedural isoproterenol (ISO) provocation tests. We analysed the clinical, electrophysiological, and procedure-related factors associated with extra-PV triggers. Results: Extra-PV triggers were documented in 11.9% (1.19 ± 0.42 foci) after de novo-AFCA and 27.0% (1.37 ± 0.65 foci) after repeat-AFCA (p = 0.004). LA volume index (OR 1.02 [1.01-1.03], p = 0.004), history of vascular disease (OR 0.55[0.31-0.91], p = 0.028) and Lead I amplitude of electrocardiogram (OR <0.01 [<0.01-0.62], p = 0.032) were independently associated with the existence of extra-PV triggers in de-novo procedure. Women (OR 1.84 [1.03-3.25], p = 0.037) and LA appendage volume (OR 1.04 [1.01-1.07] p = 0.027) were independently associated with extra-PV triggers during the redo-mapping procedure. Septum (28.4%), coronary sinus (24.0%), and superior vena cava (19.6%) were common extra-PV foci, and septal foci were more commonly found in repeat mapping (38.4% vs. 25.0%, p = 0.025). Among 65 patients who showed extra-PV at the repeat procedures, 19 (29.2%) matched with previous focal or empirical extra-PV ablation sites and 9 (13.8%) were multiple or unmappable sites. AF recurrence rates were significantly higher in both patients with extra-PV triggers after de novo procedures (Log-rank P <0.001; HR 1.93 [1.58-2.36], p= <0.001) and repeat procedures (Log-rank P <0.001, HR 1.87 [1.29-2.70], p= <0.001). Conclusion: ISO provoked extra-PV triggers commonly found in AF patients with significant remodelling and previous empirical or focal extra-PV ablations. Existence of extra-PV triggers were independently associated with poorer rhythm outcome after both de novo and repeat AFCA.